Gambaran Pengetahuan Penata Anestesi dan Perawat Icu Tentang Pengkajian Nyeri Nonverbal Adult Pain Scale Pada Pasien Tersedasi di RSUD Prof. Dr. Margono Soekarjo Purwokerto - Afandy, Dian Nurnatasha; Handayani, Rahmaya Nova; Wibowo, Tophan Heri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Background: Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage. Accurate pain assessment requires health workers to use appropriate tools tailored to the patient's condition. Purpose: To evaluate the knowledge of anesthetists and ICU nurses regarding the nonverbal pain assessment using the Nonverbal Adult Pain Scale sedated patients at RSUD Prof. Dr. Margono Soekarjo Purwokerto. Research Method: This descriptive quantitative study employed a cross-sectional design with a total sampling technique involving 85 participants. Data were collected through questionnaires. Results: The majority of participants were aged 21-30 years (40.0%), held a DIV/S1 level of education (37.6%), and had 0-5 years of experience (36.5%). Analysis revealed that 68.2% of anesthetists and ICU nurses had a good level of knowledge regarding NVPS. Knowledge was particularly strong among those aged 31-40 years, with a D4/S1 education level and 0-5 years of work experience. The majority of respondents with sufficient knowledge were aged 21-30 years, nurse education, and experience >10 years. Meanwhile, for those with less knowledge, the majority are aged 31-40 years, have a DIII education, and have work experience of 6-10 years.